Extrafiscalidade: uma observação a partir da Teoria dos Sistemas Sociais - Matsunaga, Marcos Hideo Moura (2018)
This paper aims to analyze the regulatory taxes (extrafiscality) from a Social System Theory perspective, originally conceived by Niklas Luhmann and developed by international and Brazilian scholars. The first part of the paper highlights the main aspects of the Social System Theory, starting with a brief history of the concept of system and the theoretical basis that resulted in the development, by Niklas Luhmann, of the concept of autopoietic social system. As from the idea developed within the Social System Theory of the current society as an embracing autopoietic communicational system, scattered in specialized partial autopoietic systems, the paper focus on the concept of the law as an autopoietic system and on its specialized function in the society, aiming to conciliate the view of Social System Theory and the legal scholars’ concepts about law. Once this theoretical basis is demonstrated, the paper analyzes the taxation as an overlapping point of three different social systems: law, economy and the political system. After, the paper reviews the concept of regulatory taxes (extrafiscality) and the main understandings and findings reached by national scholars on its aspects, mechanisms and particularities due to the characteristics of the different kind of taxes, as well as the principles and constitutional rules that justify its use and limits. At the end, the regulatory taxes (extrafiscality) is observed through the lens of the Social System Theory as well from the idea of tax as a structural coupling of law, politics and economy